Pandemia de la COVID-19 y salud mental: reflexiones iniciales desde la atención primaria de salud española - Buitrago Ramírez, Francisco (Aten Primaria, 2021)
An approach is made to the psychological and psychosocial characteristics that the COVID-19 pandemic is acquiring in the countries of our socio-cultural environment. The scarcity of research in this regard and the necessary acceptance of uncertainty to face the situation, both socially, as well as health and psychological, are discussed. Consequently, a series of reflections and recommendations are proposed for the psychological care of the population, health workers and social organization based on: 1) The existence of psychological and psychosocial research into connected fields and 2) In the new neuroscientific perspectives on emotions and their elaboration in crisis situations.